A Phase 1 study of intravenous infusions of tigecycline in patients with acute myeloid leukemia. (13th October 2016) - Reed, Gregory A.; Schiller, Gary J.; Kambhampati, Suman; Tallman, Martin S.; Douer, Dan; Minden, Mark D.; Yee, Karen W.; Gupta, Vikas; Brandwein, Joseph; Jitkova, Yulia; Gronda, Marcela; Hurren, Rose; et al.
Abstract: Acute myeloid leukemia (AML) cells meet the higher energy, metabolic, and signaling demands of the cell by increasing mitochondrial biogenesis and mitochondrial protein translation. Blocking mitochondrial protein synthesis through genetic and chemical approaches kills human AML cells at all stages of development in vitro and in vivo. Tigecycline is an antimicrobial that we found inhibits mitochondrial protein synthesis in AML cells. Therefore, we conducted a phase 1 dose‐escalation study of tigecycline administered intravenously daily 5 of 7 days for 2 weeks to patients with AML. A total of 27 adult patients with relapsed and refractory AML were enrolled in this study with 42 cycles being administered over seven dose levels (50–350 mg/day). Two patients experienced DLTs related to tigecycline at the 350 mg/day level resulting in a maximal tolerated dose of tigecycline of 300 mg as a once daily infusion. Pharmacokinetic experiments showed that tigecycline had a markedly shorter half‐life in these patients than reported for noncancer patients. No significant pharmacodynamic changes or clinical responses were observed. Thus, we have defined the safety of once daily tigecycline in patients with refractory AML. Future studies should focus on schedules of the drug that permit more sustained target inhibition. Abstract : In a phase I clinical trial of tigecycline administered once daily to Acute myeloid leukemia (AML) patients, the MTD was 300 mg/day. Tigecycline had a markedly shorter half‐life in AML patients due to which no significant pharmacodynamic changes or clinical responses were observed.